Extra-Low-Frequency Pulse Stimulated Conformational Change in Blood-Cell Proteins and Consequent Immune Activity Transformation - Ibtisam A. Abbas Al-Darkazly; S. M. Rezaul Hasan (IEEE Journal of Translational Engineering in Health and Medicine, 2020)
Objective: investigation of the extra-low-frequency (ELF) stimulation effect on blood-cell proteins, that causes variation in its electrostatic-state. A hypothesis that this results in the conformational change in the blood-cell proteins which could enhance immune activity is explored. Since HIV-1 and host-cell engage through charge-charge interactions, an electrical-pulse may cause charge redistribution, hypothetically resulting in host-cell proteins to be isolated from viral access. Methods: Buffy coat samples were exposed to ELF square waveform pulses of 5Hz, 10Hz and 1MHz, for 2-hours, and were then examined using immunofluorescence technique. The expression of glycoprotein CD4, and co-receptor protein CCR5, were investigated. Also, the binding activity of the N-terminal domain of CCR5 and the distribution of the nuclear-pore-complex (NPC) transport factor, FGNup153 were investigated. Comparison with control samples were carried out. Results: Increased CD4 count, which could enhance the immune system. In addition, the inability of N-terminus-specific antibody 3A9 to bind to CCR5 N-terminal, could be due to the interactions with the ELF electric-field, which may also hypothetically inhibit HIV-1 attachment. Furthermore, the electrostatic interactions between the ELF pulse and the FGNup153 induces redistribution in its disorder sequence and possibly causes conformational change. This could possibly prevent large virus particle transport through the NPC. Conclusion: Novel concept of ELF stimulation of blood cellular proteins has been developed leading to transformation of immune activity. Clinical-Impact: The translational aspect is the use of ELF as an avenue of electro-medicine and the results are a possible foundation for the clinical application of ELF stimulation in immune response.